S/10 Sculpture Today : 10th International Sculpture Conference. (Toronto : International Sculpture Center, 1978)
Allen, Karyn ; Anderson, Laurie ; Andre, Carl ; Andrews, Oliver ; Archambault, Louis ; Arn, Robert ; Banham, Reyner ; Baxter, Ian ; Bayer, Jeffrey ; Beasley, Bruce ; Morris, Robert ; Rabinowitch, David ; Trakas, George ; Simonds, Charles ; Stokes, Lou ; Smith, Brian ; Reid, Bill ; etc.
S/10 Sculpture Today : 10th International Sculpture Conference / Sculpture d'aujourd'hui : 10e conférence internationale de la sculpture, International Sculpture Center, Toronto, 31 May - 4 June 1978. Conference: Talks and Panels, Workshops, Exhibitions, Special Events, ...
English-French
kunstcatalogus